The Contribution of Implementation Adiwiyata Program on Environment Caring Character at Senior High School Adiwiyata in Pandeglang Banten - Fathurahman Bahrudin, Moh. Dendy; Hidayah, Hesti; Yusuf Prihadi, Fisabil (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Adiwiyata program was formed to form and develop the environmental caring character of school, especially learners, but the phenomenon of research in schools that are the subject of research, still violations committed by some learners that indicate the environmental caring character of learners at Adiwiyata school in Pandeglang is still low. The purpose of this study is to calculate the contribution to the formation of environmental-care characters cognitive, affective and psychomotor aspects of students in SMA Adiwiyata Pandeglang Banten. The method in this research used quantitative descriptive. The data collection used observation, questionnaire, interview, and documentation, while data analysis techniques using correlation coefficient test, regression test and coefficient of determination. The school, which is the subject of this research were two Adiwiyata schools and the other one was non-Adiwiyata in Pandeglang Banten with the sample was 325 respondents. The results of the research showed that the implementation of Adiwiyata program has a significant contribution to formation of character environmentally cognitive, affective and psychomotor learners, but its contribution is not balanced on the three aspects. Contributions Adiwiyata program was high only on cognitive and psychomotor aspects, while the contribution of affective aspect was low.